Peran Advokasi Hukum dalam Bantuan Hak Rakyat Miskin terhadap Implementasi Posbakum - Ismaidar Ismaidar; Andreas Nainggolan (Pusat Riset dan Inovasi Nasional, 2025)
An advocate is a legal professional who provides legal services both inside and outside the courtroom based on statutory law. During the Dutch colonial era, legal representation by advocates was extremely expensive, making it accessible only to individuals of high social status. At that time, indigenous people, who were generally impoverished, could not afford legal representation. However, this situation has changed with the enactment of Law No. 16 of 2011 on Legal Aid. This law guarantees the constitutional right of every individual to receive free and quality legal assistance, especially for underprivileged communities, through Legal Aid Posts (Posbakum). Advocates working at Posbakum help marginalized individuals understand their rights, provide legal consultations, and prepare essential legal documents.